2018
DOI: 10.1159/000486552
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Mannose-Binding Lectin2</i></b> Gene Polymorphism and IgG4 in Membranous Nephropathy

Abstract: Background: Idiopathic membranous nephropathy (IMN) has been linked to the lectin pathway, IgG4 and genetic susceptibility. We investigated the frequency of mannose-binding lectin2 (MBL2) gene polymorphisms and the serum ratio of IgG4 in patients with membranous nephropathy (MN). Methods: Polymorphisms in the exon 1 of the MBL2 gene (codons 52, 54, and 57) and single base polymorphisms at positions -550 (HL) and -221 (XY) in the promoter region were evaluated in 60 patients compared to a control group (CG) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…There is evidence that MBL can bind to the Fc portion of IgG, which lacks galactose residues (such as in rheumatoid arthritis) and thereby activate the LP [42]. Recently polymorphisms in the MBL2 gene in idiopathic MN and lupus MN were suggested to be associated with LP activation in MN [43].…”
Section: Membranous Nephropathymentioning
confidence: 99%
“…There is evidence that MBL can bind to the Fc portion of IgG, which lacks galactose residues (such as in rheumatoid arthritis) and thereby activate the LP [42]. Recently polymorphisms in the MBL2 gene in idiopathic MN and lupus MN were suggested to be associated with LP activation in MN [43].…”
Section: Membranous Nephropathymentioning
confidence: 99%
“…Complete remission as defined by proteinuria endpoints was more likely to occur in seropositive patients (treated with various combinations of corticosteroids, cyclophosphamide, cyclosporine and/or tacrolimus) who had lower levels of MBL, MASP-1 and MASP2 at baseline (65). Polymorphisms in the MBL2 gene were more commonly observed in patients with primary MN in one study, although correlations between MBL2 genotype, circulating MBL levels, anti-PLA2R seropositivity, and proteinuria were not made in this study (66).…”
Section: Mannose-binding Lectin and Alternative Pathway Activation In...mentioning
confidence: 56%
“…As previously discussed, the lectin pathway plays an important role in disease pathogenesis [30]. In a case-control Brazilian study, an association was noted between membranous nephropathy and mannose-binding lectin 2(MBL2) polymorphism in patients carrying O allele, in particular, A/O genotype [31]. Investigators also found a defective MBL production in patients with YA/O, XA/O, and O/O genotypes.…”
Section: Role Of Complements In the Disease Pathophysiologymentioning
confidence: 83%